Croatian Validation of tws and Predictors of Tourist Psychological Well-Being - Pedić, Paula; Penezić, Zvjezdan (Academica Turistica - Tourism and Innovation Journal, 2025)
This study aimed to validate the Croatian version of the Tourism Well-being Scale (TWS) and identify potential predictors of tourist psychological well-being. Grounded in the theoretical framework of the HOPE (Human Optimal Psychological Experiences) model, the TWS measures psychological well-being resulting from touristic activities and experiences. Four hundred Croatian-speaking adults participated in the study via Google Forms, completing the TWS, a sociodemographic questionnaire, the Flourishing Scale, the Purpose in Life test, and the Big Five Inventory (BFI). Confirmatory factor analysis initially revealed a suboptimal fit of the original one-factor model of the TWS to the data. However, the one-factor model was confirmed through modifications proposed by the scale authors. The TWS demonstrated internal consistency and congruent validity, manifesting positive correlations with meaning in life and flourishing. Examining measurement invariance across biological sexes underscored the scale’s configural, metric, and scalar invariance. Regarding predictors of tourist psychological well-being, hierarchical regression analysis indicated that extraversion and openness have positive, and neuroticism negative effects on tourist psychological well-being. Additionally, forms of tourism such as retreats, volunteer activities, charity engagements, or visits to slums significantly positively affected tourists’ psychological well-being. Age, agreeableness, and conscientiousness did not significantly predict tourist psychological well-being. This research advances tourism studies by emphasizing the importance of validating tourist-related scales across various cultural and linguistic settings. Doing so promotes the creation of reliable measurement instruments, enabling better comparisons of psychological well-being among tourists from diverse backgrounds. Also, identifying predictors of tourist psychological well-being gives essential directions for further research in the hospitality industry. Keywords: Tourism Well-being Scale, validation, measurement invariance, predictors, multiple regression analysis